Understanding Students' Difficulties and Motivation in Learning Vocabulary Through an English Song titled Lovin Myself - Ava Max: Penelitian - Jeviwnta Septi Zahran; Cici Situmorang; Muhamad Ajidin; Zavier Kevin I (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study was conducted to understand the difficulties, obstacles, and motivations of students in learning English vocabulary through the song “Lovin' Myself” by Ava Max. This study used a descriptive qualitative method, with data collection through an open questionnaire filled out by students who had experience learning vocabulary using the song. The data was then analyzed to identify learning experiences, challenges faced by students, and the impact of the song on their motivation and vocabulary comprehension. The results showed that this song served as an effective learning medium to increase students' interest and motivation because it created a more relaxed, light, and enjoyable learning environment and was often integrated into daily activities. Students found that it was easier to remember vocabulary through the rhythm, repeated lyrics, and sentence context in the song. In addition, several respondents began to improve their independent learning strategies, such as guessing the meaning of words from context before consulting a dictionary. However, this study also identified several challenges that students still frequently encounter, including fast song tempo, unclear pronunciation, and the presence of idiomatic vocabulary that is difficult to understand without additional explanation. This evidence shows that songs have great potential as vocabulary learning tools, but still need to be combined with supporting strategies.